Pengaruh Pengoperasian Wide-Body Aircraft Terhadap Kelancaran Arus Lalu Lintas Penerbangan di Makassar Air Traffic Service Center - Daniel Rumani; Hadi Prayitno; Intan Rizka Subandi (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2020)
This study aims to obtain a description of whether there is an influence between the movement of wide-body aircraft both departure and arrival on flight delays as a measure of the smooth flow of flight traffic at the Makassar Air Traffic Service Center. The research concludes that there is a positive relationship between the operation of wide-body aircraft and flight delays of 0.870. The positive correlation indicates that the more wide-body aircraft operations, the flight delay will increase, which if there is an increase in flight delays, the smooth flow of flight traffic will decrease. The coefficient of determination is 75%, which means that the effect of the operation of wide-body aircraft on flight delays is 75% and the rest is determined by other factors not included in the research section. The equation obtained from the regression test is Y = -5,679 + 1,872 X. So, if the operation of wide-body aircraft increases by 1, the flight delay will increase by 1,872 at a constant of -5,679.